Legal study of court decisions regarding errors in requests for cancellation of standard clauses in financial services sector agreements - Ninik Ayuhandika; Dahlan Dahlan; Athika Salsabilla Harahap; Rendie Meita Sarie Putri (Privietlab, 2026)
Consumers (customers) who feel disadvantaged by the standard clauses in credit (financing) agreements with financial institutions can submit a request for cancellation of the standard clauses through the Consumer Dispute Resolution Agency or Badan Penyelesaian Sengketa Konsumen (BPSK) and take legal action in the form of objections to the District Court and cassation to the Supreme Court. This study aims to describe, in detail and systematically, the legal reasons for consumers’ requests for cancellation of standard clauses and analyze the considerations of the panel of judges in decisions on requests for cancellation of standard clauses in financial services sector agreements. This study employs normative legal research with a descriptive approach. The approaches used include the statute, case, and conceptual approaches to the Cassation Decision Number 651 K/Pdt. Sus-BPSK/2013, District Court Decision No. 185/Pdt. Sus-BPSK/2016/PN-Rap and Cassation Decision No. 459 K/Pdt. Sus-BPSK/2017. Data were collected through literature and document studies and then qualitatively analyzed. The study’s results indicate that the request to annul the standard clause is based on the argument that the standard agreement made by business actors in the financial services sector contains a prohibited clause, as regulated in Article 18 of Law Number 8 of 1999 concerning Consumer Protection. However, in the three decisions, the panel of judges tended to qualify the dispute as a breach of contract or purely civil dispute, thus deeming the BPSK incompetent to examine and decide the case. This has implications for legal uncertainty regarding the limits of the BPSK's authority and the effectiveness of consumer protection in the financial services sector.